The relationship between perceived social support and women experiences in menopause - Shariat Moghani, Sedigheh; Simbar, Masuomeh; Dolatian, MahroKh; Nasiri, Malihe (Advances in Nursing & Midwifery, 2016)
Abstract: Background and Aim: Menopause is an important issue in the field of reproductive and women’s health. Social support can help to reduce post-menopausal women’ problems and improve their quality of life. The aim of this study was to investigate the relationship between social support and the experiences of menopause. Materials and Methods: This was a descriptive correlative study that was conducted in 2013 in Mashhad, Iran. 220 postmenopausal women aged 40 to 65 years were recruited through quota and community-based sampling. Data collection tools included demographic questionnaire, multidimensional social support MSPSS, and assessing the experiences of women in menopause. Validity and reliability of the questionnaires was reviewed and approved before use. Data was analyzed by SPSS 21 software using variance analysis, Spearman correlation coefficient and regression analysis at significant level of 0.05. Results: The average score of MSPSS was 59.73±15.74 and 60% of women perceived high social support. The average score of "physical and psychological experiences of women" was 33.5±18.1. There was a significant negative correlation between social support and the importance people of life(Family, neighbor, doctor,….)with women’s experiences of menopause (r= - 0/19, p= 0/006 and r=- 0/16, p= 0/01). Also, the “important people” dimension of perceived social support was a better predictor for women’s experiences in menopause. Conclusions: Perceived social support has a positive impact on menopausal experiences. "Important people" dimension was a better predictor for the women’ experiences in menopause. Key words: Health, Menopause, Social Support, Women’s Experience.